Properties and consolidation of nanostructured Ce0.8Gd0.2O1.9 by pulsed-current-activated sintering - Shon, In-Jin; Kim, Dong-Ki; Lee, Ki-Tae; Nam, Kee-Seok (Metals and materials international, 2008)
Dense nanophase Ce 0.8 Gd 0.2 O 1.9 was sintered by a pulsed-current-activated sintering method within 10 min from Ce 0.8 Gd 0.2 O 1.9 nanopowder made using the co-precipitation method. Sintering was accomplished under the combined effects of a pulsed current and mechanical pressure. Highly dense Ce 0.8 Gd 0.2 O 1.9 with a relative density of up to 96.5% was produced under the simultaneous application of 80 MPa of pressure and a pulsed current. The ionic conductivities and mechanical properties of the Ce 0.8 Gd 0.2 O 1.9 were investigated.